2021
DOI: 10.1016/j.compbiomed.2021.104518
|View full text |Cite
|
Sign up to set email alerts
|

Assessing school-based policy actions for COVID-19: An agent-based analysis of incremental infection risk

Abstract: Many schools and universities have seen a significant increase in the spread of COVID-19. As such, a number of non-pharmaceutical interventions have been proposed including distancing requirements, surveillance testing, and updating ventilation systems. Unfortunately, there is limited guidance for which policy or set of policies are most effective for a specific school system. We develop a novel approach to model the spread of SARS-CoV-2 quanta in a closed classroom environment that extends traditional transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In comparison to departments D1-D4, the reduction in average quanta inhaled by departments D5-D7 is nearly doubled. Interestingly, other ABM-based studies found similar results when analysing the duration of classes in schools [36], where shorter classes were preferable. The remaining experiments (larger building, separate workspaces, better natural ventilation, better mechanical ventilation, and wearing masks), do not show any differential aspects among departments, however, wearing masks has the largest impact on reducing quanta levels across all departments.…”
Section: Results For People/departmentssupporting
confidence: 63%
See 2 more Smart Citations
“…In comparison to departments D1-D4, the reduction in average quanta inhaled by departments D5-D7 is nearly doubled. Interestingly, other ABM-based studies found similar results when analysing the duration of classes in schools [36], where shorter classes were preferable. The remaining experiments (larger building, separate workspaces, better natural ventilation, better mechanical ventilation, and wearing masks), do not show any differential aspects among departments, however, wearing masks has the largest impact on reducing quanta levels across all departments.…”
Section: Results For People/departmentssupporting
confidence: 63%
“…Establishing a mandatory mask policy has no effect on the CO 2 level but almost completely eliminates the quanta concentration from the building, as predicted by the aerosol model developed by Peng and Jimenez [16]. Other ABM models from the literature, such as [33,34,35,36], have made similar observations regarding the use of masks.…”
Section: Results For Whole Buildingmentioning
confidence: 70%
See 1 more Smart Citation
“…With limited data due to the still-nascent rise of this pandemic, simulation models can be particularly helpful in making evidence-based decisions. Although many models for COVID have been developed or adapted in the past year and a half (e.g., [2][3][4][5][6][7]), there is a lack of models that are both agent-based (modeling individual people) and discrete-space (modeling actual, rather than idealized, spaces), a combination which helps to apply simulation to real-world contexts. One model that fills this gap is COVID-ADAPT.…”
Section: Introductionmentioning
confidence: 99%
“…With the agent model, some scholars have carried out the COVID-19 transmission simulation at a macro level [20]. However, more scholars use the agent model to study the spread and prevention and control of the COVID-19 in hospitals, schools, supermarkets, and other large public spaces by virtue of its advantages in micro-scale simulation [21][22][23][24][25][26]. In the most exciting research [27], the blood collection and diagnostic flow system in hospitals were optimized by using this system.…”
Section: Introductionmentioning
confidence: 99%